2014
DOI: 10.1177/1468794114524222
|View full text |Cite
|
Sign up to set email alerts
|

Participants’ experiences of the qualitative interview: considering the importance of research paradigms

Abstract: We used a multiple-case study to investigate participants' experiences in interviews from six qualitative studies that differed in interview orientations, designs, methods, participants, and Downloaded from Limits of the paradigm-driven approach Roulston (2010b) makes clear that the paradigm-driven approach to qualitative interviews, while helping researchers 'be better prepared to design research projects to use

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 30 publications
4
44
0
7
Order By: Relevance
“…Two recent meta-studies of the participant experience in qualitative research (Opsal et al 2015;Wolgemuth et al 2015) have found that institutional review boards (IRBs) often underestimate the benefits brought by such research, in terms for example of developing rewarding relationships, learning about issues and prompting self-reflection. When I started out on my own research project, I was, like most researchers, concerned more with avoiding harm to participants than considering what positive impact it might have on their lives.…”
Section: Implications For Future L2 Motivation Researchmentioning
confidence: 99%
“…Two recent meta-studies of the participant experience in qualitative research (Opsal et al 2015;Wolgemuth et al 2015) have found that institutional review boards (IRBs) often underestimate the benefits brought by such research, in terms for example of developing rewarding relationships, learning about issues and prompting self-reflection. When I started out on my own research project, I was, like most researchers, concerned more with avoiding harm to participants than considering what positive impact it might have on their lives.…”
Section: Implications For Future L2 Motivation Researchmentioning
confidence: 99%
“…There is potential for qualitative research to be opened up to such people, for example, those affected by military experiences, with sufficient ethical safeguards in place. Studies show that vulnerable participants can find benefit from participating, even if it is a distressing experience 41,42 . There is an important question about psychological trauma being caused by catastrophic diagnosis, frightening medical treatments, and symptoms such as breathlessness , 32,43,44 which requires investigation in regard to mesothelioma.…”
Section: Discussionmentioning
confidence: 99%
“…Es decir, el paradigma de investigación son los lentes a través de los cuales el investigador observa el mundo y que, por lo tanto, influirá en su modo de observar su objeto de investigación. Para varios autores, el investigador deberá posicionar, de manera fundamentada su paradigma en alguno de las siguientes opciones: positivismo y postpositivismo, constructivismo social y teoría critica (Wolgemuth et al 2015). La principal diferencia entre las opciones señaladas es que, mientras las posiciones positivista y postpositivista consideran que hay una sola verdad absoluta y una única manera de alcanzar el conocimiento, el constructivismo y la teoría crítica creen que existen diversas verdades y conocimientos que son socialmente construidos, y para los cuales existen diversos modos de llegar (Hays y Singh, 2012, p. 40).…”
Section: El Paradigma De Investigaciónunclassified